The integration of Social Network Services (SNSs) in the ESL writing classroom: A qualitative study on UiTM English lecturers and students / Wan Nurul Firdaus Wan Moud Naim - Wan Mohd Naim, Wan Nurul Firdaus (2015)
Technology advancement specifically in Social Network Services (SNSs) offers global materials and a natural context to promote students’ writing skills in the ESL classroom. However, not many educators in higher education institutions in Malaysia utilize the technology to enhance students’ English language skills particularly in writing. This study sets out to explore the English lecturers’ and students’ perception on the integration of SNSs in the ESL writing classroom in Universiti Teknologi Mara Campuses in Malaysia. The researcher applies a qualitative approach whereby to achieve the objective of the study, the required qualitative data were collected through nonstructured interview sessions, online discussion and via email responses. The questions have been designed to seek responses on the types of social-network related activities normally conducted by the lecturers, perceptions related to the strength and weaknesses of the integration of SNSs in the ESL writing classroom, views from the lecturers on the usefulness, effectiveness, ease of use and accessibility, students’ participation and involvement and interaction between the lecturer and the students, and finally the students’ perception on the usefulness, effectiveness, ease of use and accessibility, lecturer’s involvement and feedback and interaction between the lecturer and the students. The analysis of the data revealed that both the lecturers and students view the integration of SNSs in the ESL writing classroom optimistically. Nevertheless, the main concern highlighted was due to poor internet connection which hinders the lecturer to make use of SNSs in the learning process. With the qualitative data presented in this study, SNSs can be used as an interactive instructional tool to promote students’ writing skills in the ESL writing classroom. It is suggested that future research should focus on the effectiveness of integrating SNSs to enhance other language skills such as reading, listening and speaking. Apart from that, future research could consider exploring how students who are majoring in English perceived the use of SNSs in the ESL writing classroom to enhance their writing skills. In addition, experimental research could also be carried out to investigate the effectiveness of SNSs in the ESL writing classroom as compared to the traditional classroom approach.